Munāẓara-yi Baḥr al-ʿulūm Sayyid Muḥammad Mahdī Burūjirdī Ṭabāṭabāʾī (1212 HQ) bā Yahūdiyān-i Dhu ʼl-Kifl : Guzārishhā-yi ʿArabī u Fārsī - al-Ṭabāṭabāʾī, Sayyid Muḥammad Mahdī al-Ḥusaynī (Miras Maktoob, ISBN: 9789004365452., 2019)
In the history of Islam, Muslim-Jewish polemics have been documented from the earliest times and studies on this subject abound. The present work is a case in point. In the spring of the year 1211/1796, the famous Shīʿī scholar Sayyid Muḥammad Mahdī al-Ḥusaynī al-Ṭabāṭabāʾī (d. 1212/1797) was on his way from Mashhad to visit the holy shrine of Imam Ḥusayn in Karbala, accompanied by a flock of his senior students. When they reached the town of al-Kifl, less than 20 km north of Najaf and home to a community of over 3.000 Jews, a delegation of the latter came to see Ṭabāṭabāʾī in the caravanserai where was staying, wishing to engage in a debate with him. The text presented here is an account of Ṭabāṭabāʾī's detailed listing of the contradictions and errors in Judaism as seen by him, a listing that remained largely unanswered. Arabic text, with a Persian translation from before 1238/1822-3.